Amyloid β-Peptide Impairs Glucose Transport in Hippocampal and Cortical Neurons: Involvement of Membrane Lipid Peroxidation - Mark, Robert J. (J Neurosci, 1997)
A deficit in glucose uptake and a deposition of amyloid β-peptide (Aβ) each occur in vulnerable brain regions in Alzheimer’s disease (AD). It is not known whether mechanistic links exist between Aβ deposition and impaired glucose transport. We now report that Aβ impairs glucose transport in cultured rat hippocampal and cortical neurons by a mechanism involving membrane lipid peroxidation. Aβ impaired (3)H-deoxy-glucose transport in a concentration-dependent manner and with a time course preceding neurodegeneration. The decrease in glucose transport was followed by a decrease in cellular ATP levels. Impairment of glucose transport, ATP depletion, and cell death were each prevented in cultures pretreated with antioxidants. Exposure to FeSO(4), an established inducer of lipid peroxidation, also impaired glucose transport. Immunoprecipitation and Western blot analyses showed that exposure of cultures to Aβ induced conjugation of 4-hydroxynonenal (HNE), an aldehydic product of lipid peroxidation, to the neuronal glucose transport protein GLUT3. HNE induced a concentration-dependent impairment of glucose transport and subsequent ATP depletion. Impaired glucose transport was not caused by a decreased energy demand in the neurons, because ouabain, which inhibits Na(+)/K(+)-ATPase activity and thereby reduces neuronal ATP hydrolysis rate, had little or no effect on glucose transport. Collectively, the data demonstrate that lipid peroxidation mediates Aβ-induced impairment of glucose transport in neurons and suggest that this action of Aβ may contribute to decreased glucose uptake and neuronal degeneration in AD.